Fulfillment of Disability Rights through Sekaa Janger Kolok Towards Sustainable Development - Aristiani, Made Diah; Yuga, Kadek Vijananda Garba; Sudharani, Made Gita; Dewi, Putu Ratih Kumala (The Sunan Ampel Review of Political and Social Sciences, 2023)
Cases of inequality in the social environment are still frequently encountered, especially for people with disabilities. The stigma against people with disabilities has led to the emergence of various assumptions stating that people with disabilities are not capable of carrying out tasks on an equal basis with normal people. Disability groups often experience discrimination in society and are marginalized in development. There is one village that is unique, this village is in Bengkala Village, Buleleng Regency, Bali Province. This village is known for having a population of residents who have had limited speech and hearing since birth. It is said that this phenomenon is caused by local endogamous marriage practices that have persisted from generation to generation in a relatively small population. This group is able to develop through social and cultural life that has been preserved from generation to generation based on uniqueness and diversity by forming a source of creative activity through "Sekaa Janger Kolok". The aim of this research is to examine efforts for social inclusion of disabled people in Bengkala Village through Sekaa Janger Kolok. The research boundary is Bengkala Village, Buleleng Regency, Bali Province, Indonesia. With a descriptive qualitative research method using data collection through primary data through interviews with Village Heads, Sekaa Chairmen, Teachers as well as secondary data from literature searches. The concepts used are rights for people with disabilities, social inclusion, social welfare. As for the findings from this research, people with disabilities were involved and empowered with the formation of Sekaa Janger Kolok and were involved in tourist villages.